La masculinité hégémonique : lecture critique d’un concept de Raewyn Connell - Demetrakis Z. Demetriou (Genre, Sexualité et Société)
Raewyn Connell’s concept of « hegemonic masculinity » represents the most influential and popular part of her work. It has been used in empirical research ranging from the areas of sexuality and gay studies to that of criminology and prison sociology. Yet, although numerous empirical researchers have made use of this concept, there has been almost no attempt to evaluate its theoretical merit. This article offers a detailed theoretical exposition as well as a critique of the concept of hegemonic masculinity. The author argues that hegemonic masculinity is not a purely white or heterosexual configuration of practice but it is a hybrid bloc that unites practices from diverse masculinities in order to ensure the reproduction of patriarchy. In the final part of the article, the author undertakes a brief case study in order to show the contribution of gay masculinities to the formation of the contemporary hegemonic bloc.